Weighted Product sebagai Metode Pendukung Keputusan untuk Menentukan Kualitas Kinerja Guru - Surya Gusti; Hambali Hambali; Sri Rezki Maulina Azmi (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
SMA Negeri 3 Tanjungbalai is a school located in Tanjungbalai City. Every year, the Principal holds a Teacher Performance Assessment to improve quality education. However, Teacher Performance Assessment is still done manually. The purpose of this research is to build a decision support system for teacher performance assessment to assist the process in determining the quality of performance with the weighted product method. The teacher performance appraisal process is applied in the form of a web application and using the SDLC model, namely planning, analysis, design, implementation, testing and management. Data collection techniques were carried out by means of interviews, observations and literature studies. And system testing is done using blackbox, based on blackbox testing, all functionality can run as expected. The value obtained is in the form of ranking the performance results with the best quality using a decision support system with a computerized weighted product method. The result of this study is to produce a decision support system that can produce information on teacher performance appraisal decisions in determining quality with a weighted product at SMA Negeri 3 Tanjungbalai. The decision support system made is able to provide convenience in the assessment process and can be used as needed.